2016
DOI: 10.1111/tog.12250
|View full text |Cite
|
Sign up to set email alerts
|

Biologics in pregnancy for the obstetrician

Abstract: Key content The authors discuss commencing biologics in pregnancy and the potential side effects. Infection is a particular risk, which may be atypical or present atypically. While there is no evidence of teratogenicity, these drugs cross the placenta and neonatal cord drug levels may exceed those of maternal drug levels. If possible, anti‐tumour necrosis factor (TNF) agents should be discontinued midtrimester but the gestation to which each drug can be used is slightly different. Neonates exposed in utero t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Biological drugs are IgG antibodies; IgA is the predominant immunoglobulin excreted in breast milk. The very low concentrations of anti-TNF molecules that may be present in breastmilk are unlikely to be absorbed orally or to result in neonatal immunosuppression, and studies assessing the effects of anti-TNF agents on breastfed infants have provided substantial reassurance 44 45. A prospective study found that breastfed infants of mothers receiving biologics (eg, infliximab, adalimumab and ustekinumab), immunomodulators or combination therapies had similar risks of infection and rates of milestone achievement at 12 months compared with non-breastfed infants or infants unexposed to these drugs 46.…”
Section: Is Ibd Medication Safe With Breast Feeding?mentioning
confidence: 99%
“…Biological drugs are IgG antibodies; IgA is the predominant immunoglobulin excreted in breast milk. The very low concentrations of anti-TNF molecules that may be present in breastmilk are unlikely to be absorbed orally or to result in neonatal immunosuppression, and studies assessing the effects of anti-TNF agents on breastfed infants have provided substantial reassurance 44 45. A prospective study found that breastfed infants of mothers receiving biologics (eg, infliximab, adalimumab and ustekinumab), immunomodulators or combination therapies had similar risks of infection and rates of milestone achievement at 12 months compared with non-breastfed infants or infants unexposed to these drugs 46.…”
Section: Is Ibd Medication Safe With Breast Feeding?mentioning
confidence: 99%
“…This review paper will endeavour to summarise the European League Against Rheumatism (EULAR) and British Society in Rheumatology (BSR) guidelines 2016 shown in Table 3 24,25,47 and focus on developments since publication of the guidelines. Supplementary Table 1.…”
Section: Latest Updates On Biologic Agentsmentioning
confidence: 99%
“…However, basic physiology indicates that breastmilk is predominantly IgA (not IgG1); the large structure of most biologic molecules means that they are less likely to be excreted in breastmilk. Additionally, such large proteinaceous molecules are denatured and digested by passage through the infant's gastrointestinal tract and therefore do not attain significant levels in breastfed infants, 47 and hence why parenteral administration is necessary to achieve a therapeutic response. All breastmilk studies completed to date have borne this out by consistently showing a steady decline in breastfed infant drug levels despite ongoing maternal dosing.…”
Section: Childhood Infections and Vaccinationsmentioning
confidence: 99%
“…Enfeksiyona meyil yaptığı da bilinen bu ilaçların kullanılması gereken durumlarda eczacının daha dikkatli olması gerekmektedir. 22 Gebelikte ilacın embriyo ve fetüs üzerine etkisi, maruz kalınan madde kadar gestasyon yaşı ile de ilişkilidir. 19 Örneğin; blastogenezis döneminde (fertilizasyondan yaklaşık 15-21 gün sonrası) ilacın etkisi "hep ya da hiç prensibi"ne göre gerçekleşmekte; bir başka deyişle embriyo ölmekte ya da etkilenmeden yaşamaya devam etmektedir.…”
Section: Gebeli̇kte Oluşan Farmakoki̇neti̇k/farmakodi̇nami̇k Deği̇şi̇...unclassified